2022
DOI: 10.1212/wnl.0000000000200340
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebral Collateral Cascade

Abstract: Background and Purpose:Robust cerebral collaterals are associated with favorable outcomes in patients with acute ischemic stroke due to large vessel occlusion treated by thrombectomy. However, collateral status assessment mostly relies on single imaging biomarkers and a more comprehensive holistic approach may provide deeper insights into the biology of collateral perfusion on medical imaging. Comprehensive collateralization is defined as blood flow of cerebral arteries through the brain tissue and into draini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 32 publications
(51 reference statements)
2
22
0
Order By: Relevance
“…We have recently described the CCC, which combines information about the quality of PAC bringing blood to ischemic brain, the robustness of TLC as the blood flows into capillaries, and how well VO occurs. 26 We will now discuss 3 critical stages of the CCC in more detail. These stages are PAC, TLC, and VO.…”
Section: Stroke Pathophysiology and The Comprehensive Collateral Cascadementioning
confidence: 99%
“…We have recently described the CCC, which combines information about the quality of PAC bringing blood to ischemic brain, the robustness of TLC as the blood flows into capillaries, and how well VO occurs. 26 We will now discuss 3 critical stages of the CCC in more detail. These stages are PAC, TLC, and VO.…”
Section: Stroke Pathophysiology and The Comprehensive Collateral Cascadementioning
confidence: 99%
“…Combining the 3 may offer a better predictor of clinical and radiologic outcomes in patients undergoing thrombectomy. This intriguing hypothesis drives the recent article by Faizy et al 1 published in this issue of Neurology® , which builds on prior work by these authors.…”
mentioning
confidence: 55%
“…That is an exciting future, but in the meantime, we need a deeper understanding of the CCC and its implications. Studies like that of Faizy et al 1 help illuminate the path forward.…”
mentioning
confidence: 96%
“…While Tan score and HIR in adult patients has been strongly correlated, discrepancies have also been reported. Faizy et al 27 reported that patients with a mixed favorable/unfavorable "collateralome" appear to have worse radiographic and clinical outcomes than those with uniformly favorable collateral parameters.…”
Section: Discussionmentioning
confidence: 99%